Hyperdemocracy - Welch, Stephen; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2013)
This book argues that a well-educated citizenry and freer flow of information has contributed to a state of'hyperdemocracy' which impedes itself. This book applies the idea of'reflexive modernization' to democratic theory, setting out a new perspective on the challenges democracy faces.
Keywords: Science; Science, general